Effect of swine-origin probiotic Pediococcus acidilactici FT28 on maintenance of antioxidant status, blood haematology and biochemical profile in early weaned grower-finisher pigs - DOWARAH, RUNJUN; VERMA, A K; AGARWAL, NEETA; SINGH, P (The Indian Journal of Animal Sciences, 2018)
An experiment was conducted with early weaned crossbred piglets (36) to evaluate antioxidant status and blood biochemical profile in grower-finisher pigs. The piglets were distributed into three groups (4 replicates of 3 each) and supplemented with basal diet either without probiotics (T0) or with a probiotic of dairy based (Lactobacillus acidophilus NCDC-15; T1) or swine based (Pediococcus acidilactici FT28; T2). Blood was collected at 45, 90 days (grower phase) and 136, 180 days (finisher phase) of feeding and analysed for various antioxidants and metabolites. Results of the study revealed that supplementation of probiotics improved superoxide dismutase (SOD), catalase and reduced glutathione (GSH) activity in early weaned grower-finisher pigs. Whereas, GSH activity was better in P. acidilactici FT28 fed group compared to L. acidophilus fed group. Serum glucose level was reduced in both T1 and T2 groups compared to control, which was further reduced in T2 group compared to T1. The total protein, albumin and globulin level in serum remained higher in T2 group in comparison to other dietary groups. Serum triglyceride and LDL-cholesterol was lower in P. acidilactici FT28 fed group. The HDL-cholesterol level was better by probiotic supplementation in grower-finisher pigs. It was concluded that supplementation of hostorigin probiotic was effective to reduce stress besides having potential to improve blood biochemical profile.